Implementasi instrumen akreditasi Perpustakaan SMA di Kecamatan Tualang Kabupaten Siak - Inten Suseno; Nining Sudiar; Rosman H (Libraria: Jurnal Ilmu Perpustakaan dan Informasi, 2022)
This study aims to find out about the implementation of library accreditation instruments at the SMA/MA level in Kec. Tualang Sakti Kab. Siak. The research method uses a quantitative descriptive research. The results showed that of the 10 schools that had been studied, not all of them implemented library accreditation. The average of the percentages seen, the 6 components contained in the school library instrument at the SMA/MA level as a whole school does not exceed the NA value ? 60 or in the overall estimation of the instrument components not more than 50%.